The effect of a beta-lactamase inhibitor peptide on bacterial membrane structure and integrity: a comparative study - SARIYAR AKBULUT, BERNA (WILEY, 2017)
Co-administration of beta-lactam antibiotics and beta-lactamase inhibitors has been a favored treatment strategy against beta-lactamase-mediated bacterial antibiotic resistance, but the emergence of beta-lactamases resistant to current inhibitors necessitates the discovery of novel non-beta-lactam inhibitors. Peptides derived from the Ala46-Tyr51 region of the beta-lactamase inhibitor protein are considered as potent inhibitors of beta-lactamase; unfortunately, peptide delivery into the cell limits their potential. The properties of cell-penetrating peptides could guide the design of beta-lactamase inhibitory peptides. Here, our goal is to modify the peptide with the sequence RRGHYY that possesses beta-lactamase inhibitory activity under in vitro conditions. Inspired by the work on the cell-penetrating peptide pVEC, our approach involved the addition of the N-terminal hydrophobic residues, LLIIL, from pVEC to the inhibitor peptide to build a chimera. These residues have been reported to be critical in the uptake of pVEC. We tested the potential of RRGHYY and its chimeric derivative as a beta-lactamase inhibitory peptide on Escherichia coli cells and compared the results with the action of the antimicrobial peptide melittin, the beta-lactam antibiotic ampicillin, and the beta-lactamase inhibitor potassium clavulanate to get mechanistic details on their action. Our results show that the addition of LLIIL to the N-terminus of the beta-lactamase inhibitory peptide RRGHYY increases its membrane permeabilizing potential. Interestingly, the addition of this short stretch of hydrophobic residues also modified the inhibitory peptide such that it acquired antimicrobial property. We propose that addition of the hydrophobic LLIIL residues to the peptide N-terminus offers a promising strategy to design novel antimicrobial peptides in the battle against antibiotic resistance. Copyright (c) 2017 European Peptide Society and John Wiley & Sons, Ltd.
Keywords: beta-lactamase; antibiotic resistance; delivery; antimicrobial peptide; cell-penetrating peptide; CELL-PENETRATING PEPTIDES; AMOXICILLIN-CLAVULANIC ACID; VIVO PROTEIN TRANSDUCTION; ANTIMICROBIAL PEPTIDES; ESCHERICHIA-COLI; IN-VIVO; STREPTOCOCCUS-PNEUMONIAE; ANTIBACTERIAL ACTIVITY; STAPHYLOCOCCUS-AUREUS; DRUG DISCOVERY